Glucagon receptor family (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The glucagon family of receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on the Glucagon receptor family [159]) are activated by the endogenous peptide (27-44 aa) hormones glucagon, glucagon-like peptide 1, glucagon-like peptide 2, glucose-dependent insulinotropic polypeptide (also known as gastric inhibitory polypeptide), GHRH and secretin. One common precursor (GCG) generates glucagon, glucagon-like peptide 1 and glucagon-like peptide 2 peptides [116]. For a recent review on review the current understanding of the structures of GLP-1 and GLP-1R, the molecular basis of their interaction, and the signaling events associated with it, see de Graaf et al., 2016 [87].